2008
DOI: 10.1128/mcb.00740-07
|View full text |Cite|
|
Sign up to set email alerts
|

Inducible Expression of Chimeric EWS/ETS Proteins Confers Ewing's Family Tumor-Like Phenotypes to Human Mesenchymal Progenitor Cells

Abstract: Ewing's family tumor (EFT) is a rare pediatric tumor of unclear origin that occurs in bone and soft tissue. Specific chromosomal translocations found in EFT cause EWS to fuse to a subset of ets transcription factor genes (ETS), generating chimeric EWS/ETS proteins. These proteins are believed to play a crucial role in the onset and progression of EFT. However, the mechanisms responsible for the EWS/ETS-mediated onset remain unclear. Here we report the establishment of a tetracycline-controlled EWS/ETS-inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 47 publications
0
71
0
Order By: Relevance
“…During the preparation of our manuscript, we noticed 2 recent publications that investigated the overexpression of EWS/FLI1 in human MSCs (32,33). Both observed that this overexpression did not transform MSC and lead to tumorigenicity.…”
Section: Discussionmentioning
confidence: 98%
“…During the preparation of our manuscript, we noticed 2 recent publications that investigated the overexpression of EWS/FLI1 in human MSCs (32,33). Both observed that this overexpression did not transform MSC and lead to tumorigenicity.…”
Section: Discussionmentioning
confidence: 98%
“…Expression data were obtained from the Gene Expression Omnibus (GEO) database. 42 The used data sets 19,[43][44][45][46][47][48][49][50][51][52][53][54][55] are summarized in Table 1. Primary data analysis was performed with Expression Console (Affymetrix) applying the Microarray Suite 5 algorithm.…”
Section: Cells and Cell Culture Pbmc DC Eft Cell Lines A673mentioning
confidence: 99%
“…In order to investigate the impact of EFT-specific fusion proteins on the expression of CTA, GEO data sets from EWS-ETS transgenic MSC were analyzed. 19,42 Expression data sets from EWSR1-FLI1 transgenic MSC and expression data sets from EWSR1-ERG transgenic MSC were analyzed. Probe sets with signal intensities below 100 in the experimental situations were excluded from analysis.…”
mentioning
confidence: 99%
“…To analyze the data, we used agglomerative hierarchical clustering and principal component analysis (PCA) using NIA Array Analysis Tools provided by the National Institute on Aging (Bethesda, MD). 11 Reverse Transcriptase-PCR RNA was converted to cDNA and amplified using the Titan One Tube RT-PCR System (Roche Diagnostics, Indianapolis, IN). The products were resolved by electrophoresis on a 1.5% agarose gel and visualized with ethidium bromide.…”
Section: Surface Epitopesmentioning
confidence: 99%